How do Medical Students Perceive Professional Attitudes? A Multi-Center Study - (:unkn) unknown (KUWAIT MEDICAL ASSOC, 2010)
Objectives: To determine the attitude of students from different medical schools towards the medical profession and evaluate the effect of gender and year of medical education Design: Multi-center cross-sectional study Setting: Six medical schools located in different geographical regions of Turkey Subjects: All the first and final year medical students (n = 1941) at these schools participated after the study protocol was approved in these schools Interventions: A Medical Profession Attitude Scale (MPAS) was administered to the students to determine the attitude of students towards the medical profession. Another questionnaire was established to see any association between attitudes and demographic characteristics. Mann-Whitney U test was used for the statistical analysis done using the SPSS for PC 13.0. Main Outcome Measures: Attitude of students towards the medical profession, the year at the medical school and gender Results: 78.7% of the first and final year students could be accessed. The Cronbach alpha reliability coefficient for the freshmen and seniors was 0.94 and 0.95, respectively, and 0.95 for the whole group. First year students' scores for all subscales were significantly higher. Similarly, the female students had higher scores. Conclusions: Final year students' lower scores may be related to concerns regarding confidence and competence arising during the clinical years where self-image as a doctor evolves. Providing professional education during the medical course becomes an increasingly important issue to prevent deterioration in professional attitudes. The individual qualifications, values, attitudes and behaviour will improve in the following years.
Keywords: attitude scales; attitude towards medical profession; HUMANISM; SCHOOL